GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Association between cardiovascular-kidney-metabolic syndrome and risks of 14 age-related health outcomes in primary prevention older population - Zhen Zhou; Kevan R. Polkinghorne; Andrew M. Tonkin; Robyn L. Woods; Anping Cai; Sophia Zoungas; Michelle A. Fravel; Michael E. Ernst; Chao Zhu; Mark Nelson; Johannes T. Neumann; Kerry M. Sheets; et al. (GeroScience, 2026)

Terrigenous inputs link nutrient dynamics to microbial communities in a tropical lagoon - Christian John; Nyssa J. Silbiger; Thomas C. Adam; Danielle M. Barnas; Kalia S. Bistolas; Robert C. Carpenter; Noe Castañeda; Megan J. Donahue; Mary K. Donovan; Lauren N. Enright; Hannah E. Epstein; Jordan P. Gallagher; et al. (Limnology and Oceanography, 2025)
Nutrient availability drives community structure and ecosystem processes, especially in tropical lagoons that are typically oligotrophic but often receive allochthonous inputs from land. Terrestrially derived nutrients are introduced to tropical lagoons by surface runoff and submarine groundwater discharge, which are influenced by seasonal precipitation. However, terrigenous inputs presumably diminish along the onshore–offshore gradients within lagoons. We characterized nutrient availability in the lagoons of a tropical high island, Moorea, French Polynesia, using spatially distributed measurements of nitrogen content in the tissues of a widespread macroalga during the rainy season over 4 yr. We used synoptic water column sampling to identify associations among macroalgal nutrient content and the composition of inorganic macronutrients, dissolved organic matter, and microbial communities. We paired these data with quantifications of land use in nearby watersheds to uncover links between terrestrial factors, aquatic chemistry, and microbial communities. Algal N content was highest near shore and near large, human‐impacted watersheds, and lower at offshore sites. Sites with high algal N had water columns with high nitrite + nitrate, silicate, and increased humic organic matter (based on a fluorescence Humification Index), especially following rain. Microbial communities were differentiated among nearshore habitats and covaried with algal N and water chemistry, supporting the hypothesis that terrigenous nutrient enrichment shapes microbial dynamics in otherwise oligotrophic tropical lagoons. This study reveals that land–sea connections create nutrient subsidies that are important for lagoon biogeochemistry and microbiology, indicating that future changes in land use or precipitation will modify ecosystem processes in tropical lagoons.

Applying the science impact framework to understand real-world applications and impacts of ICESat and ICESat-2 data on decision-making - Siobhan L. Light; Molly E. Brown; Aimee R. Neeley; Thomas A. Neumann (Remote Sensing Applications: Society and Environment, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Healthy environments for athleTes (HEAT): environmental conditions along a 90 km ultra-marathon event, South Africa - H. Havenga; D. Gharbi; N. Sewry; B. Language; F. H. Neumann; J. M. Finch; T. Hill; J. Boulter; E. Jordaan; S. J. Piketh; M. Schwellnus; R. P. Burger (International Journal of Biometeorology, 2024)
This paper provides an overview of the HEAT (Healthy Environments for AthleTes) project, which aims to understand the impact of environmental conditions on athlete health and performance during major sporting events such as long-distance running, cycling, and triathlons. In collaboration with the SAFER (Strategies to reduce Adverse medical events For the ExerciseR) initiative, the HEAT project carried out a field campaign at the 2022 Comrades Marathon in the KwaZulu-Natal province of South Africa. The measurement campaign deployed seven weather stations, seven PM 2.5 monitors and one spore trap along the 90 km route to capture spatially representative measurements of complex micro-climates, allergenic aerospora, and particulate matter exposure. The results indicate that runners were exposed to moderate risk heat stress conditions. Novel findings from this initial campaign shows elevated and potentially harmful PM 2.5 levels at spectator areas, possibly coinciding with small fire events around the race day festivities. Our findings show values PM 2.5 levels over the WHO 24-h guidelines at all stations, while 2000 µg/m 3 at two stations. However, the lack of an acute exposure standard means direct health impacts cannot be quantified in the context of a sport event. The HEAT project highlights important aspects of race day monitoring; regional scale climatology has an impact on the race day conditions, the microclimatic conditions (pollution and meteorology) are not necessarily captured by proximity instruments and direct environmental measurements are required to accurately capture conditions along the route.

Role of indigenous microorganisms and organics in the release of iron and trace elements from sediments impacted by iron mine tailings from failed Fundão dam - Alex S. Santos; Bernardo F. Braz; Pedro Sanjad; Ana Caroline R. Cruz; Miriam A.C. Crapez; Reiner Neumann; Ricardo E. Santelli; Carolina N. Keim (Environmental Research, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis - S. Callegaro; H. H. Svensen; E. R. Neumann; A. G. Polozov; D. A. Jerram; F. M. Deegan; S. Planke; O. V. Shiganova; N. A. Ivanova; N. V. Melnikov (Contributions to Mineralogy and Petrology, 2021)
A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin center and periphery, recovered from 15 deep sills intercepted by boreholes. The studied samples are all low-Ti basalt and basaltic andesites, confirming absence of high-Ti and alkaline STLIP magmatism in the Tunguska Basin. The sills derive from picritic parental melts produced by extensive melting of a mantle source with recycled crustal components below a thinned lithosphere (50–60 km), within the spinel stability field. The mantle source was dominantly peridotitic, with enriched pyroxenitic domains formed by recycled lower crust, in agreement with previous models for the main tholeiitic STLIP phase. Limited amounts (up to 5%) of highly radiogenic granitoids or moderately radiogenic metapelites were assimilated in upper crustal magma reservoirs. After emplacement, sills intruded in Cambrian evaporites assimilated marlstones and interacted with the evaporitic host rocks, probably via fluids and brines. This is the first time that such process is described in subvolcanic rocks from all across the volcanic basin. The sills are correlated geochemically with the established chemostratigraphy for the on-craton STLIP lava piles and intrusions (Norilsk region). Sills correlated with the Morongovsky–Mokulaevsky Fm. and the Norilsk-type intrusions are the most voluminous, present all across the central Tunguska Basin, and bear the strongest evidence of interaction with evaporites. Massive discharge of thermogenic volatiles is suggested by explosive pipes and hydrothermal vent structures throughout the Tunguska Basin. We propose that this voluminous pulse of magmatism is a good candidate for the hitherto unidentified early intrusive phase of the STLIP, and may link the deep Tunguska basin sills to the end-Permian environmental crisis.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Contrasting arsenic cycling in strongly and weakly stratified contaminated lakes: Evidence for temperature control on sediment–water arsenic fluxes - P. M. Barrett; E. A. Hull; K. Burkart; O. Hargrave; J. McLean; V. F. Taylor; B. P. Jackson; J. E. Gawel; R. B. Neumann (Limnology and Oceanography, 2019)
Arsenic contamination of lakebed sediments is widespread due to a range of human activities, including herbicide application, waste disposal, mining, and smelter operations. The threat to aquatic ecosystems and human health is dependent on the degree of mobilization from sediments into overlying water columns and exposure of aquatic organisms. We undertook a mechanistic investigation of arsenic cycling in two impacted lakes within the Puget Sound region, a shallow weakly stratified lake and a deep seasonally stratified lake, with similar levels of lakebed arsenic contamination. We found that the processes that cycle arsenic between sediments and the water column differed greatly in shallow and deep lakes. In the shallow lake, seasonal temperature increases at the lakebed surface resulted in high porewater arsenic concentrations that drove larger diffusive fluxes of arsenic across the sediment–water interface compared to the deep, stratified lake where the lakebed remained ~10°C cooler. Plankton in the shallow lake accumulated up to an order of magnitude more arsenic than plankton in the deep lake due to elevated aqueous arsenic concentrations in oxygenated waters and low phosphate : arsenate ratios in the shallow lake. As a result, strong arsenic mobilization from sediments in the shallow lake was countered by large arsenic sedimentation rates out of the water column driven by plankton settling.

Extracellular Matrix Expression and Production in Fibroblast-Collagen Gels: Towards an In Vitro Model for Ligament Wound Healing - Stephanie M. Frahs; Julia Thom Oxford; Erica E. Neumann; Raquel J. Brown; Cynthia R. Keller-Peck; Xinzhu Pu; Trevor J. Lujan (Annals of Biomedical Engineering, 2018)

Benefits of greenhouse gas mitigation on the supply, management, and use of water resources in the United States - K. Strzepek; J. Neumann; J. Smith; J. Martinich; B. Boehlert; M. Hejazi; J. Henderson; C. Wobus; R. Jones; K. Calvin; D. Johnson; E. Monier; et al. (Climatic Change, 2015)

Combined effects of global climate change and regional ecosystem drivers on an exploited marine food web - Susa Niiranen; Johanna Yletyinen; Maciej T. Tomczak; Thorsten Blenckner; Olle Hjerne; Brian R. MacKenzie; Bärbel Müller‐Karulis; Thomas Neumann; H. E. Markus Meier (Global Change Biology, 2013)
Changes in climate, in combination with intensive exploitation of marine resources, have caused large‐scale reorganizations in many of the world's marine ecosystems during the past decades. The B altic S ea in N orthern E urope is one of the systems most affected. In addition to being exposed to persistent eutrophication, intensive fishing, and one of the world's fastest rates of warming in the last two decades of the 20th century, accelerated climate change including atmospheric warming and changes in precipitation is projected for this region during the 21st century. Here, we used a new multimodel approach to project how the interaction of climate, nutrient loads, and cod fishing may affect the future of the open C entral B altic S ea food web. Regionally downscaled global climate scenarios were, in combination with three nutrient load scenarios, used to drive an ensemble of three regional biogeochemical models ( BGM s). An Ecopath with Ecosim food web model was then forced with the BGM results from different nutrient‐climate scenarios in combination with two different cod fishing scenarios. The results showed that regional management is likely to play a major role in determining the future of the Baltic Sea ecosystem. By the end of the 21st century, for example, the combination of intensive cod fishing and high nutrient loads projected a strongly eutrophicated and sprat‐dominated ecosystem, whereas low cod fishing in combination with low nutrient loads resulted in a cod‐dominated ecosystem with eutrophication levels close to present. Also, nonlinearities were observed in the sensitivity of different trophic groups to nutrient loads or fishing depending on the combination of the two. Finally, many climate variables and species biomasses were projected to levels unseen in the past. Hence, the risk for ecological surprises needs to be addressed, particularly when the results are discussed in the ecosystem‐based management context.

The production and turnover of extramatrical mycelium of ectomycorrhizal fungi in forest soils: role in carbon cycling - A. Ekblad; H. Wallander; D. L. Godbold; C. Cruz; D. Johnson; P. Baldrian; R. G. Björk; D. Epron; B. Kieliszewska-Rokicka; R. Kjøller; H. Kraigher; E. Matzner; et al. (Plant and Soil, 2013)

Foraging behavior of golden hamsters (Mesocricetus auratus) in the wild - S. C. Larimer; P. Fritzsche; Z. Song; J. Johnston; K. Neumann; R. Gattermann; M. E. McPhee; R. E. Johnston (Journal of Ethology, 2011)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Bee-hawking by the wasp, Vespa velutina, on the honeybees Apis cerana and A. mellifera - K. Tan; S. E. Radloff; J. J. Li; H. R. Hepburn; M. X. Yang; L. J. Zhang; P. Neumann (The Science of Nature, 2007)

Gigantism in honeybees: Apis cerana queens reared in mixed-species colonies - Ken Tan; H. R. Hepburn; Shaoyu He; S. E. Radloff; P. Neumann; Xiang Fang (The Science of Nature, 2006)

Heat-balling wasps by honeybees - Tan Ken; H. R. Hepburn; S. E. Radloff; Yu Yusheng; Liu Yiqiu; Zhou Danyin; P. Neumann (The Science of Nature, 2005)

The Skien lavas, Oslo Rift: petrological disequilibrium and geochemical evolution - E. Dunworth; E.-R. Neumann; J. Rosenbaum (Contributions to Mineralogy and Petrology, 2001)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

Absconding in honeybees ( Apis mellifera ) in relation to queen status and mode of worker reproduction - H. R. Hepburn; S. L. Reece; P. Neumann; R. F. A. Moritz; S. E. Radloff (Insectes Sociaux, 1999)

Silicic melts produced by reaction between peridotite and infiltrating basaltic melts: ion probe data on glasses and minerals in veined xenoliths from La Palma, Canary Islands - E. Wulff-Pedersen; E. -R. Neumann; R. Vannucci; P. Bottazzi; L. Ottolini (Contributions to Mineralogy and Petrology, 1999)

Origin and implications of mafic xenoliths associated with Cenozoic extension-related volcanism in the Vlencia Trough, NE Spain - E. -R. Neumann; J. Mart; J. Mitjavila; E. Wulff-Pedersen (Mineralogy and Petrology, 1999)

Annexin V and vesicle membrane electroporation - K. Tönsing; S. Kakorin; E. Neumann; S. Liemann; R. Huber (European Biophysics Journal, 1997)